PERGESERAN INDUSTRI KONVENSIONAL MENJADI GREEN INDUSTRI - Hendro Murtiono; Atik Suprapti; Suzanna Ratih Sari; Resha Rizkiyanto (Jurnal Arsitektur ARCADE, 2023)
Abstract: The concept of conventional industry, which is still managed traditionally, is that waste treatment is still managed individually and stops until the waste is disposed of in landfills. The location of the industrial area has also not been utilized properly so that it can increase income from the industry it produces. The eco-green industrial park concept, which has been widely implemented and developed in Europe, America, and Asia, offers a concept to improve industrial economic performance in an industrial area while minimizing the negative impact on the environment where the industry is located. The development of conventional industries into green industries is expected to reduce the potential for environmental damage and pollution arising from these industrial activities and can be minimized in proportion to the economic benefits obtained by the industry. The application of industrial concepts can be viewed from various aspects, namely the extent to which industrial activities can be integrated with natural systems, energy systems used, material flow and waste management in all industrial areas, water use, the effectiveness of industrial green management, material use, and building technology, as well as the extent of integration with the surrounding community.Keyword: Conventional, Green IndustryAbstrak: Konsep industri konvensional, yang dikelola secara tradisional, dimana pengolahan limbah dikendalikan secara individual serta berhenti sampai limbah tersebut dibuang di tempat pembuangan sampah. Lokasi area industri juga tidak dipilihkan secara benar sehingga kurang dapat meningkatkan pendapatan dari industri yang ada. Konsep eco-green industrial park, yang banyak diterapkan serta dikembangkan di Eropa, Amerika, serta Asia, menawarkan konsep meningkatkan kinerja ekonomi industri di area industri serta meminimalkan dampak negatif lingkungan. Perkembangan industri konvensional menjadi industri hijau diharapkan mampu mengurangi potensi kerusakan lingkungan serta polusi yang timbul dari kegiatan industri, serta diharapkan meningkatkan secara proporsional manfaat ekonomi dari industri tersebut. Aplikasi konsep industri dapat dilihat secara multi aspek, diantaranya sejauh mana kegiatan industri dapat diintegrasikan dengan sistem alam, sistem energi yang digunakan, aliran material serta pengelolaan limbah industri, penggunaan air, efektivitas manajemen hijau, bahan penggunaan, serta teknologi bangunan, serta integrasi dengan masyarakat sekitar.Kata Kunci: Konvensional, Industri Hijau